Defining Major Oil and Gas Companies’ Development Strategies in the Era of Energy Transition - V. I. Salygin; D. S. Lobov (Vestnik MGIMO-Universiteta)
The energy market today is turbulent. Nations follow different energy trends and shape their policies towards Energy Transition and sustainable development. To avoid risks and pursue opportunities, oil and gas companies must adapt their longterm strategies to macro-trends and national regulations.The study's objective is to investigate how major oil and gas companies’ development trends correlate with trends and strategies at the national level. The hypothesis is that oil and gas companies’ operations and innovation portfolios are linked to national energy mixes and environmental regulations. To do this, the authors examined the energy markets of 54 countries with the focus on Brazil, Canada, China, EU, Norway, Russia, Saudi Arabia, the UK, the USA, operational indicators, and innovation development trends of 18 major oil and gas companies. The production volumes have been translated into an ordinal scale and analyzed with the use of Spearman correlation.The study confirmed a weak correlation between oil and gas companies' operational indicators and national strategies. Companies operating in countries with strict environmental regulations, primarily in the European Economic Area, have been more likely to adapt their businesses to energy transition while building up oil and gas production; they also have had more diversified innovation portfolios. As more countries moved towards later generations of environmental regulations, the increase in renewable energy investments was found in more oil and gas majors.